A Casebook for Comparative Politics - Johnson, Mark L; Pashayan, Angela; Pedreira, Daniel I; Schuster, Matthew; Tures, John; Handel, Cheryl Van Den; Chang, Helen; Hendrickson, Petra; Gritter, Matthew (Opendora, 2025)
This book is intended to serve as a companion text for courses in Comparative Politics, Introduction to Political Science, and similar subjects. The target audience is lower-division undergraduates. Each chapter constitutes a single country (case), with material on seven (7) major topics: History, Identity, Culture and Civil Society, Participation, Formal Institutions, Political Economy, and Foreign Relations.